Best Answer

Let's say you want the standard form of the equation x2 + 10x + y + 20 = 0.

x2 + 10x + y + 20 = 0 (add 5 and subtract y to both sides)

x2 + 10x + 25 = -y + 5 (form the square to the left, and factor out -1 to the right)

(x + 5)2 = -(y - 5) which is in the standard form (x - h)2 = 4p(y - k), where (h, k) = (-5, 5) is the vertex, and 4p = -1 yields p = -1/4, so the parabola opens downward.

Q: What is the standard form of x2 10x y 200?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

X2 + 10X - 13 = 17 add 13 to each side X2 + 10X = 30 halve the linear coefficient ( 10 ), square it and add it to both sides X2 + 10X + 25 = 30 + 25 factor on the left and gather terms on the right (X + 5)2 = 55 (X + 5)2 - 55 = 0 ---------------------------vertex form, (- 5, - 55 ), is the vertex -------------------------------------------[-------------------------------]

This can be factored in multiple ways, depending on the signs. X2+10x+25 factors into (x+5)2 or (x+5)(x+5). X2-10x+25 factors into (x-5)2 or (x-5)(x-5). If 25 is being subtracted, then the trinomial is impossible to factor.

(x + 2)(x - 12)

Equations with an order of 2 (contains a value to the power of 2, i.e. x2). An example of a quadratic equation is: x2 + 10x + 7

if y = x2 + 10x + 25 then y = (x + 5)2 This tells us that the graph would be a parabola, with it's vertex at (-5, 0), and a range of 0 to infinity.

Related questions

x2 - 10x - 6 = 2x + 1 Subtracting 2x + 1 from both sides gives: x2 - 12x - 7 = 0

It is: x2-10x+21 = 0 and the value of x is 3 or 7 when solved

Given: x2 + 10x - 16 Let: x2 + 10x - 16 = 0 x2 + 10x - 16 = 0 ∴ x2 + 10x + 25 = 16 + 25 ∴ (x + 5)2 = 41 ∴ x = -5 ± √41 ∴ x2 + 10x - 16 = (x + 5 + √41)(x + 5 - √41)

x2+10x-336

The LCM is x^3 - 100x

x2 + 10x + 25 --> (x + 5)2

x2+10x-24 = (x-2)(x+12) when factored

y=x2-10x+30=(x-5)2-25+30=(x-5)2+5

x2 + 9 = 10x x2 - 10x + 9 = 0. (x - 9)(x - 1) = 0. Therefore, x = 1 or 9.

x2 + 10x = 0 x2 + 10x + 25 = 25 (x + 5)2 = 25 x + 5 = +-5 x1 = 0 x2 =10

x2 + 10x + 21 = (x + 3)(x + 7)

12